The Effect of Combination of Aerobic and Strengthening Exercise on Muscle Strength, Balance, and Sleep Quality in Individuals with Type 2 Diabetes - Miray Budak; Merve Yılmaz Menek (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: The aim of this study was to determine the effects of aerobic and strengthening exercise combination on glycosylated hemoglobin (HbA1c), muscle strength, balance, and sleep quality in individuals diagnosed with type 2 diabetes mellitus (DM). Material and Methods: Fifty individuals aged between 30 and 65 years and diagnosed with type 2 DM were included in this study. Anthropometric measurements, HbA1c, quadriceps and hamstring muscle strength, balance, and sleep quality of the included individuals were evaluated. Aerobic and strengthening exercises were applied to the participants 3 days a week for 12 weeks. All evaluation measurements were repeated at the end of 12 weeks. Results: Of the 50 individuals included in this study and diagnosed with type 2 DM, 64% (n=32) were male and 36% (n=18) were female. The mean age of the participants was 50.12±10.81 years, the mean body mass index was 29.97±3.12 kg/m2, the waist/hip ratio was 0.91±0.08, and the mean HbA1c was 9.19±2.39. When the pre and post-treatment HbA1c, muscle strength, balance, and sleep quality measurements of all participants were compared, there were statistically significant differences (p<0.001). Conclusion: It was determined that the combination of long-term aerobic and strengthening exercise decreased the HbA1c value and also significantly improved muscle strength, balance, and sleep quality in individuals with type 2 DM. A structured exercise program that includes strengthening and aerobic exercises would be beneficial in developing the most effective and appropriate exercise prescriptions in terms of exercise efficiency and sustainability for individuals with type 2 DM.